Preparation method of high-wear-resistance flame-retardant environment-friendly graphene / basalt fiber / rubber composite material and prepared laminated conveyor belt
Through the application of graphene and basalt fiber composite materials, the shortcomings of flame retardant conveyor belts in the prior art in terms of mechanical strength, wear resistance and anti-static performance are solved, and the comprehensive performance of high wear resistance, flame retardant and anti-static is achieved. Suitable for harsh environments underground in coal mines.
Patent Information
- Application Number
- CN202411550377.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to provide excellent mechanical mechanical strength, wear resistance and anti-static effects while ensuring high flame retardant performance. Especially in harsh environments under coal mines, the flame retardant efficiency of traditional flame retardant conveyor belts is low and easy to cause Static combustion explosion accident.
The core frame material, core glue and cover glue of the conveyor belt are used to combine graphene and basalt fibers for the core skeleton material, core glue and cover glue. Graphene is modified by chemical grafting method, combining the conductive oxide characteristics of basalt fibers to form high strength, high modulus and resistance. High temperature, flame retardant, antistatic composite material.
It achieves comprehensive performance of high wear resistance, flame retardant and anti-static, meets the high standard needs of flame retardant laminated conveyor belts for underground coal mines, extends the service life of the conveyor, and reduces the wear and energy consumption of the equipment.
Smart Images

Figure CN119431906A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame-retardant conveyor belts, and in particular to a preparation method of a highly wear-resistant, flame-retardant and environmentally friendly graphene / basalt fiber / rubber composite material and a prepared laminated conveyor belt. Background Art
[0002] Conveyor belt is a special material, and one of its largest applications is above and below the coal mine. Due to the generally poor transportation conditions in coal mines and the high concentration of gas in coal mines, fire has become a major hidden danger that threatens life and production safety. According to investigations, a large part of coal mine fires are caused by conveyor belts. Therefore, it is particularly important to develop conveyor belt products with flame retardant properties.
[0003] The domestic flame retardant belt industry has experienced a rapid technological development process and has now developed to the fifth generation of products. The fifth generation of flame retardant conveyor belts mainly include three types: steel cord conveyor belts, whole core belts and laminated belts. Steel cord conveyor belts have high strength, good impact resistance, and the longest service life of the three belts. They are suitable for modern long-distance, large-volume and high-speed transportation environments. However, their high cost, heavy belt body, inconvenient disassembly, and high energy consumption are the main factors restricting the use and development of steel cord conveyor belts. The low tear strength of steel cord conveyor belts has also become an important factor that makes it difficult to be widely used over a large area. The whole core flame retardant conveyor belt has good flame retardant properties, a light belt body, and a simple preparation process, but it is easy to slip, has poor flex resistance, unstable operation, and a short service life. These are inherent defects that are difficult to avoid through technical processing. Compared with the above two types of conveyor belts, the strength of fabric laminated flame retardant conveyor belt is second only to that of steel cord flame retardant conveyor belt, but the belt body is thinner than the whole core belt, and has the tear strength that is difficult to achieve with steel cord conveyor belt and the quick joint and joint safety factor that cannot be achieved with the whole core belt. Moreover, it has stable operation and long service life, which effectively reduces the transportation load of the conveyor, reduces the wear and energy consumption of the equipment, and prolongs the service life of the conveyor. It can be called "energy-saving conveyor belt". With the improvement of flame retardant technology and the use of new flame retardant materials, the flame retardancy of fabric laminated flame retardant belt is no longer a problem. There are many research results on general-purpose flame retardant conveyor belts at home and abroad, while there are relatively few research reports on flame retardant laminated conveyor belts for underground coal mines. This is mainly because compared with general-purpose flame retardant conveyor belts, the flame retardant performance requirements of coal mine underground belts are higher, and the flame retardant efficiency of ordinary laminated flame retardant conveyor belts is low, and it is more difficult to meet the underground application standards. Traditional conveyor belts based on halogen flame retardant have a single flame retardant component, low flame retardant efficiency, and produce a large amount of smoke. Halogen-free rubber needs to be filled with a large amount of flame retardant to achieve excellent flame retardant properties, which makes it difficult to meet the flame retardant and durability standards of underground coal mine conveyor belts. In addition, in the harsh environment of coal mines with gas, combustion and explosion accidents are often caused by static electricity on the surface of the material. Therefore, flame retardant laminated conveyor belts for underground coal mines also need good anti-static effects, which also brings new difficulties and challenges to the development of flame retardant laminated conveyor belts for underground coal mines. From the above analysis, it can be seen that how to ensure high flame retardancy while ensuring excellent mechanical strength, wear resistance and anti-static effects is still a difficult problem that urgently needs to be solved in this field.
[0004] Basalt fiber is an inorganic fiber. It is made of natural basalt ore. After crushing it, it is added to the melting furnace. After melting at 1450-1500℃, it is made through a platinum-rhodium alloy wire drawing plate. It does not contain any additives. It is the only green and healthy glass fiber product that is non-polluting and non-carcinogenic. It can be called the "green and environmentally friendly industrial raw material" in the 21st century. It is the fourth high-tech fiber after aramid, carbon fiber, and ultra-high molecular weight polyethylene fiber. Basalt fiber has the characteristics of high strength, high elastic modulus, good temperature resistance, and not easy to deform. In addition, basalt fiber contains nearly 20% conductive oxides, which can reduce the generation of static electricity in production, which is of great significance for the anti-static in the mandatory requirements of safe production in the coal industry. Secondly, basalt fiber has excellent flame retardant properties, and the oxygen index can be as high as 43. It is a non-combustible fiber, has no melting dripping when heated, has strong resistance to heat shrinkage, and does not produce toxic gases when heated. It is a very advantageous skeleton material for flame-retardant conveyor belts.
[0005] Graphene is a carbon nanomaterial with excellent mechanical strength (180GPa) and modulus (1TPa), as well as a large specific surface area. It is currently recognized as one of the materials with the highest mechanical properties and one of the best mechanical reinforcement or enhancement materials. It has important application prospects in materials science, micro-nano processing, energy, biomedicine and drug delivery, and is considered to be a revolutionary "king of new materials" in the future. There has been no public report on the research of improving the mechanical properties of basalt fiber by introducing graphene and combining the performance advantages of the two for use in the core skeleton material of conveyor belts. Summary of the invention
[0006] In order to make up for the deficiencies of the prior art, the present invention provides a method for preparing a highly wear-resistant, flame-retardant and environmentally friendly graphene / basalt fiber / rubber composite laminated conveyor belt. By compositely using graphene and basalt fiber in the core skeleton material, core rubber and cover rubber of the conveyor belt, the conveyor belt is endowed with the characteristics of high strength, high modulus, high temperature resistance, non-deformation, environmental protection, flame retardancy and antistatic, thereby meeting the application requirements of rubber conveyor belts in different use environments and solving the problems existing in the prior art.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0008] A method for preparing a highly wear-resistant, flame-retardant and environmentally friendly graphene / basalt fiber / rubber composite material is provided, which is characterized by comprising the following steps:
[0009] (1) Preparation of functionalized graphene@basalt fiber particles
[0010] ① Using chemical grafting method to in-situ modify the graphene surface with silane coupling agent and sulfur to obtain a bifunctional modified graphene dispersion;
[0011] ② Add basalt fiber particles treated with different impregnants into the bifunctional modified graphene dispersion, the mass ratio of basalt fiber particles to graphene (solid state) is 20:1-50:1, adjust the pH to 10-12, stir at room temperature for 1-3 hours, and then filter and remove the residue after sand grinding to obtain a mixed solution of functionalized graphene@basalt fiber particles;
[0012] (2) Preparation of graphene@basalt fiber / rubber composites
[0013] ① Using the mixed solution of functionalized graphene@basalt fiber particles obtained in step (1) as a dispersion, adding a certain amount of natural latex; wherein the mass ratio of graphene@basalt fiber particles (solid mass) to natural latex is 1:2-1:5, mechanically stirring at room temperature for 1-3 hours to obtain a stable graphene@basalt fiber / natural latex suspension, flocculating with calcium chloride solution, repeatedly washing until neutral, and drying to prepare graphene@basalt fiber / natural rubber masterbatch;
[0014] ② Taking natural rubber as the matrix material, the graphene@basalt fiber / natural rubber masterbatch with different contents is added to control the graphene@basalt fiber composite particles to be a variable of 10 to 40phr; wherein, the compounding agent is 3-5 parts of zinc oxide, 1-2 parts of stearic acid, 0.5-1 parts of accelerator D, 0.5-1 parts of accelerator DM, and 1.5-3 parts of sulfur; the graphene@basalt fiber / natural rubber mixture is prepared by a melt method, the vulcanization conditions are 145°C, 10MPa, and the time is the positive vulcanization time T90, and the graphene@basalt fiber / natural rubber composite material is prepared.
[0015] Furthermore, the specific operation of step (1) is as follows:
[0016] S1 ultrasonically disperses the aqueous dispersions of graphene with different oxygen contents at room temperature to obtain graphene dispersions;
[0017] S2: adding a certain amount of silane coupling agent to the graphene dispersion, stirring and reacting for 1-3 hours at a certain temperature to obtain a silane coupling agent-modified graphene dispersion;
[0018] S3 will a certain amount of Na 2 S 2 O 3 The aqueous solution was added to the silane coupling agent-modified graphene dispersion of S2 and stirred for 1 h;
[0019] S4: adding a certain amount of hydrochloric acid to the mixed solution, and continuing to stir at room temperature for 2 hours after the addition is completed, so as to form bifunctional modified graphene double-modified with silane coupling agent and sulfur particles.
[0020] Furthermore, in step S1, the oxygen content in the aqueous dispersion of graphene with different oxygen contents is 10%-25%; the concentration of the aqueous dispersion of graphene with different oxygen contents is 2mg / mL to 6mg / mL.
[0021] Furthermore, in step S2, the amount of silane coupling agent used is 2%-6% of the mass of graphene; and the stirring reaction temperature is 60-90°C.
[0022] Further, in step S3, Na 2 S 2 O 3 The concentration of aqueous solution is 0.4~0.8mmol / mL, Na 2 S 2 O 3 The amount used is 2%-6% of the mass of graphene; in step S4, hydrochloric acid and Na 2 S 2 O 3 The molar ratio is 1:4.
[0023] Furthermore, in step (2), the natural rubber in ② is replaced by mixed rubber, and the weight proportion of the mixed rubber is: 20-50 parts of natural rubber, 20-50 parts of butadiene rubber, and 20-50 parts of styrene-butadiene rubber.
[0024] Furthermore, the basalt fiber particles treated with different impregnants in step (2) are basalt fiber particles for asphalt, basalt fiber particles for cement, basalt fiber particles with roving for profiles, or basalt fiber particles with roving for textiles.
[0025] The present invention also provides a laminated conveyor belt, which is made by the above-mentioned preparation method.
[0026] Furthermore, the preparation operation of the above-mentioned laminated conveyor belt is as follows:
[0027] The conveyor belt is made of basalt fiber cloth treated with rubber as the core skeleton material, and graphene@basalt fiber / rubber composite material as the core rubber and cover rubber.
[0028] Furthermore, the specific preparation operation of the above-mentioned laminated conveyor belt is as follows: graphene @ basalt fiber / rubber composite material is used as the core rubber and cover rubber of the laminated conveyor belt, basalt fiber cloth is used as the core skeleton material of the laminated conveyor belt, and a multi-layer sandwich-type laminated rubber conveyor belt structure is arranged on a calender, and the basalt fiber cloth is 1, 3, 5 odd layers; the vulcanization conditions are 135-150°C, the vulcanization pressure is 1-3MPa, and the vulcanization time is 30-60 minutes.
[0029] Beneficial effects of the present invention:
[0030] The present invention develops a new type of highly flame-retardant, anti-static, high-strength, high-wear-resistant, environmentally friendly and multifunctional laminated rubber conveyor belt for coal mines. The lightweight, high-strength, corrosion-resistant, high-temperature-resistant and highly flame-retardant basalt fiber cloth is used as the core skeleton material of the laminated conveyor belt. Compared with the traditional fabric core, it has higher mechanical strength, temperature resistance and flame retardancy; at the same time, the graphene @ basalt fiber / rubber composite material is used as the core rubber and cover rubber of the laminated conveyor belt. Compared with the rubber used for traditional transmission belts, it has better comprehensive properties such as strength, anti-static, wear resistance and flame retardancy; through the combination of the above two new materials, the laminated conveyor belt with a new structure is developed. The belt body is light, flame-retardant and anti-static, and it has stable operation and long service life. It can effectively reduce the transportation load of the conveyor, reduce the wear and energy consumption of the equipment, and extend the service life of the conveyor. It can be called a "green energy-saving conveyor belt". With the development of the green and low-carbon economy, environmentally friendly and multifunctional rubber conveyor belts will surely have a broader market and competitiveness.
[0031] In addition, the highly flame retardant, antistatic, high-strength, high-wear-resistant and environmentally friendly rubber conveyor belt developed by the present invention has excellent weather resistance, high and low temperature resistance, oil resistance, etc. by regulating the compounding and proportioning of the rubber matrix. It is suitable for different application places and is widely used in many fields such as docks, building materials, metallurgy, and electric power, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a scanning electron microscope image of the cover rubber of the graphene@basalt fiber / rubber composite material;
[0033] Figure 2 This is a scanning electron microscope image of a sandwich-type laminated rubber conveyor belt;
[0034] Figure 3 It is a schematic diagram of the structure of the graphene@basalt fiber / rubber composite laminated conveyor belt of the present invention. DETAILED DESCRIPTION
[0035] In order to clearly illustrate the technical features of the present invention, the present invention is described in detail below through specific implementation methods in conjunction with the accompanying drawings.
[0036] The experimental raw materials used in the present invention are shown in Table 1 below.
[0037] Table 1 Experimental raw materials
[0038]
[0039] Example 1
[0040] A method for preparing a highly wear-resistant, flame-retardant and environmentally friendly graphene / basalt fiber / rubber composite material comprises the following steps:
[0041] (1) Preparation of functionalized graphene@basalt fiber particles
[0042] ① Preparation of double-modified graphene dispersion
[0043] A graphene aqueous dispersion (2 mg / mL) with an oxygen content of 20% was ultrasonically dispersed at room temperature to obtain a graphene dispersion. A silane coupling agent with a mass percentage of 4% of graphene (solid) was added to the graphene dispersion solution and stirred at 80°C for 2 hours. Then, Na 2 S 2 O 3 The aqueous solution was added to the above silane coupling agent modified graphene dispersion and stirred for 1h, wherein Na 2 S 2 O 3 The mass of graphene (solid state) is 4%. Then, a certain amount of hydrochloric acid (with Na 2 S 2 O 3 The molar ratio of the two is 1:4), and after the addition is completed, mechanical stirring is continued at room temperature for 2 hours to obtain a graphene dispersion double-modified with a silane coupling agent and sulfur particles.
[0044] ② Preparation of mixed solution of graphene@basalt fiber composite particles
[0045] Asphalt basalt fiber particles were added into the double-modified graphene dispersion, the mass ratio of basalt fiber particles to graphene was 40:1, the pH value of the solution was adjusted to 10 with NaOH, mechanically stirred at room temperature for 1 hour, and then filtered and deslagging after sand grinding to obtain a mixed solution of graphene@basalt fiber composite particles.
[0046] (2) Preparation of graphene@basalt fiber / rubber composites
[0047] ① Preparation of graphene@basalt fiber / natural rubber masterbatch
[0048] A certain amount of natural latex was added to the above-prepared stably dispersed functionalized graphene @ basalt fiber composite particle suspension, wherein the mass ratio of graphene @ basalt fiber composite particles (solid mass) to natural latex was 1:2, and mechanical stirring was performed at room temperature for 1 hour to obtain a stable graphene @ basalt fiber / natural latex suspension, flocculated with 10wt% calcium chloride solution, repeatedly washed until neutral, and dried to prepare graphene @ basalt fiber / natural rubber masterbatch.
[0049] ② Preparation of graphene@basalt fiber / natural rubber composites
[0050] Natural rubber was used as the matrix material, and a certain amount of graphene @ basalt fiber / natural rubber masterbatch was added, and the content of graphene @ basalt fiber composite particles in the natural rubber matrix was controlled to be 20phr; wherein, the compounding agents were 5 parts of zinc oxide, 1 part of stearic acid, 0.5 parts of accelerator D, 0.5 parts of accelerator DM, and 2 parts of sulfur; the graphene @ basalt fiber / natural rubber mixture was prepared by a melt method, and the vulcanization conditions were 145℃, 10MPa, and the time was 8 minutes to prepare the graphene @ basalt fiber / natural rubber composite material.
[0051] According to the performance test and the results in Table 2, the graphene@basalt fiber / natural rubber composite material prepared by the method of this embodiment solves the contradiction that it is difficult to optimize the durability and functionality (such as antistatic and flame retardant) of the laminated rubber conveyor belt at the same time. The functional modification of the graphene@basalt fiber composite particles enables a better interface bonding with the rubber matrix, ensuring better mechanical properties and lower wear, with a tensile strength of 23.1MPa, a tear strength of 36.43N / mm, and a DIN wear of 0.109cm 3 At the same time, nearly 20% of the conductive oxide in basalt fiber can reduce the generation of static electricity, making the resistance value of the composite material <3.0×10 8 Ω, the excellent flame retardant properties of basalt fiber itself make the oxygen index of graphene@basalt fiber / natural rubber composite material reach the flammable level of 24.
[0052] Example 2
[0053] Natural rubber was used as the matrix material, a certain amount of graphene@basalt fiber / natural rubber masterbatch was added, and the content of graphene@basalt fiber composite particles in the natural rubber matrix was controlled to be 30 phr. The rest of the operations were the same as in Example 1.
[0054] From the results in Table 2, we can see that as the content of graphene@basalt fiber composite particles increases to 30phr, the oxygen index of the composite material further increases to 26, which is a flammable level. However, due to the difference in modulus between filler and rubber, the mechanical properties of the composite material slightly decrease, with a tensile strength of 19.4MPa, a tear strength of 31.21N / mm, and a DIN abrasion loss of 0.146cm. 3 But it is still the effective range of rubber conveyor belts.
[0055] Example 3
[0056] After the dual-modified graphene dispersion is prepared, the cement basalt fiber particles are added into the dual-modified graphene dispersion, and the remaining operations are the same as in Example 1.
[0057] Compared with basalt fiber particles for asphalt, the impregnation agent used for basalt fiber for cement is different, which leads to a slight difference in the mechanical properties of graphene@basalt fiber / natural rubber composite material with that in Example 1, but it is still within the effective range of rubber conveyor belts, and the resistance value of the composite material is <3.0×10 8 Ω, which can effectively prevent the generation of static electricity, and the oxygen index is 24, which is a flammable level. That is, the graphene@basalt fiber / natural rubber composite material prepared by treating basalt fiber without a wetting agent solves the contradictory problem that the durability and functionality (such as antistatic and flame retardant) of the laminated rubber conveyor belt are difficult to optimize at the same time.
[0058] Example 4
[0059] After the double-modified graphene dispersion is prepared, the profile roving basalt fiber particles are added into the double-modified graphene dispersion, and the remaining operations are the same as in Example 1.
[0060] Compared with the basalt fiber particles used for asphalt, the impregnating agent used for the untwisted roving basalt fiber used for profiles is different. The graphene@basalt fiber / natural rubber composite material prepared by treating the basalt fiber without an impregnating agent solves the contradictory problem that it is difficult to simultaneously optimize the durability and functionality (such as antistatic and flame retardancy) of the laminated rubber conveyor belt.
[0061] Example 5
[0062] After the double-modified graphene dispersion is prepared, the textile roving basalt fiber particles are added into the double-modified graphene dispersion, and the remaining operations are the same as in Example 1.
[0063] The impregnating agents used for untwisted basalt fibers for textile use are different. The graphene@basalt fiber / natural rubber composite material prepared by treating the basalt fibers without using an impregnating agent solves the contradictory problem that the durability and functionality (such as antistatic and flame retardancy) of the laminated rubber conveyor belt are difficult to optimize at the same time.
[0064] Example 6
[0065] In order to reduce the cost and take the comprehensive performance into consideration, the natural rubber is partially replaced by butadiene rubber and styrene-butadiene rubber. The mixed rubber is composed of 30% butadiene rubber, 40% natural rubber and 30% styrene-butadiene rubber by mass percentage. The preparation process of the graphene@basalt fiber / rubber composite material is the same as that in Example 1, wherein during the melt mixing process, the compounding agent is 4 parts of zinc oxide, 1.5 parts of stearic acid, 1 part of accelerator CZ, 1 part of accelerator DM and 2 parts of sulfur.
[0066] As cis-1,4-butadiene rubber and styrene-butadiene rubber partially replace natural rubber, the mechanical properties of the composite material slightly decrease, with a tensile strength of 16.2 MPa and a tear strength of 22.69 N / mm, but it is still within the effective range of rubber conveyor belts, and the DIN wear, oxygen index and resistance value do not change much. This shows that the rubber matrix can be adjusted to meet the application requirements of rubber conveyor belts in different use environments.
[0067] Example 7
[0068] A laminated conveyor belt is prepared by using a basalt fiber cloth treated with a resin as a core skeleton material of the conveyor belt, and using any of the graphene@basalt fiber / rubber composite materials prepared in Examples 1-6 as core rubber and cover rubber. The graphene@basalt fiber / rubber composite material prepared in Example 1 is used as an example, and the specific preparation process is as follows:
[0069] Graphene@basalt fiber / rubber composite material is used as the core rubber and cover rubber of the laminated conveyor belt, basalt fiber cloth is used as the core skeleton material of the laminated conveyor belt, and the calender is arranged in a multi-layer sandwich-type laminated rubber conveyor belt structure, with basalt fiber cloth as one layer; the vulcanization conditions are 145°C, the vulcanization pressure is 3MPa, and the vulcanization time is 40 minutes.
[0070] See also Figure 1 , which is a scanning electron microscope image of the cover rubber of the graphene@basalt fiber / rubber composite material. From the low-magnification scanning electron microscope, it can be observed that the basalt fibers are evenly distributed and generally in an oriented state. From the high-magnification scanning electron microscope, it can be observed that the basalt fibers are tightly combined with the rubber matrix, indicating that the basalt fibers are well combined with the rubber matrix after being modified by the graphene dispersion, ensuring the mechanical properties of the composite material.
[0071] See also Figure 2 , which is a scanning electron microscope image of a sandwich-type laminated rubber conveyor belt. From a low-magnification scanning electron microscope, it can be observed that the basalt fiber cloth is in a multi-layer woven state, sandwiched between two layers of covering rubber. From a high-magnification scanning electron microscope, it can be observed that the space between the basalt fiber cloths is filled with rubber materials, indicating that the calendering process can achieve the preparation of a sandwich-type laminated rubber conveyor belt. The prepared rubber laminated conveyor belt was evaluated for application. The bonding strength between the conveyor belt cloth layers is ≥5.0N / mm; the bonding strength between the covering layer and the cloth layer is ≥3.0N / mm; the oxygen index is greater than 28; the average value of the upper and lower surfaces is not greater than 3.0×10 8 Ω; transverse tensile strength>260N / mm, longitudinal tensile strength>600N / mm, meeting the performance requirements of laminated rubber conveyor belts. Figure 3 The structure of the laminated conveyor belt is shown schematically.
[0072] Comparative Example 1
[0073] With natural rubber as the matrix material, a certain amount of graphene @ basalt fiber / natural rubber masterbatch was added, and the content of graphene @ basalt fiber composite particles in the natural rubber matrix was controlled to be 10 phr. The rest of the operations were the same as in Example 1. When the content of graphene @ basalt fiber composite particles in the natural rubber matrix was 10 phr, the mechanical properties of the composite material were good, but the oxygen index was 20, which was flammable, and the resistance value was >3.0×10 8 Ω, it cannot effectively prevent the occurrence of static electricity, indicating that a certain content of graphene @ basalt fiber is the key factor for the anti-static and flame retardant functions of rubber conveyor belts.
[0074] Comparative Example 2
[0075] With natural rubber as the matrix material, 20phr of asphalt basalt fiber is directly mixed with natural rubber to prepare a basalt fiber / natural rubber mixture, wherein the compounding agents are 5 parts of zinc oxide, 1 part of stearic acid, 0.5 parts of accelerator D, 0.5 parts of accelerator DM, and 2 parts of sulfur. The vulcanization conditions are vulcanization temperature of 145℃, vulcanization pressure of 10MPa, and vulcanization time of 7 minutes and 40 seconds to prepare a basalt fiber / natural rubber composite material. The performance test of the composite material prepared by directly mixing 20phr of basalt fiber with natural rubber without reinforcement and modification of graphene dispersion is shown in Table 2. The mechanical properties are greatly reduced, the tensile strength is 13.9MPa, and the tear strength is 16.54N / mm, which cannot meet the use requirements of rubber conveyor belts. Moreover, the direct compounding of basalt fiber with rubber has poor interface bonding, which leads to the failure of the flame retardant and electrostatic properties of basalt fiber to play, and the use requirements of rubber conveyor belts cannot be met.
[0076] Comparative Example 3
[0077] The same as step (1) in Example 1, ① obtain a graphene dispersion double-modified with a silane coupling agent and sulfur particles, add a certain amount of natural latex to the above-prepared stably dispersed functionalized graphene suspension, wherein the mass ratio of graphene to natural latex is 1:10, and mechanically stir at room temperature for 1 hour to obtain a stable graphene / natural latex suspension, flocculate with 10wt% calcium chloride solution, repeatedly wash until neutral, and dry to prepare a graphene / natural rubber masterbatch.
[0078] Natural rubber is used as a matrix material, and a certain amount of graphene / natural rubber masterbatch is added to control the content of graphene in the natural rubber matrix to be 5phr; the compounding agents include 5 parts of zinc oxide, 1 part of stearic acid, 0.5 parts of accelerator D, 0.5 parts of accelerator DM, and 2 parts of sulfur; the graphene / natural rubber mixture is prepared by a melt method, and the vulcanization conditions are as follows: a vulcanization temperature of 145°C, a vulcanization pressure of 10MPa, and a vulcanization time of 8 minutes and 30 seconds, to prepare a graphene / natural rubber composite material.
[0079] The composite material prepared by compounding the double-modified graphene dispersion as a reinforcing filler with rubber greatly improved the mechanical properties of the rubber matrix, with a tensile strength of 30.7MPa and a tear strength of 39.45N / mm. However, the oxygen index of the composite material is only 19, which is flammable, and the resistance value is high, which cannot effectively release static electricity.
[0080] Combining Comparative Examples 2 and 3, it can be seen that the preparation of composite materials by compounding graphene-functionalized basalt fiber particles with rubber is the key to solving the contradictory problem that the durability and functionality (such as antistatic and flame retardancy) of laminated rubber conveyor belts are difficult to optimize at the same time.
[0081] Table 2 Experimental data
[0082]
[0083]
[0084] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for preparing a highly wear-resistant, flame-retardant and environmentally friendly graphene / basalt fiber / rubber composite material, characterized in that: The steps are as follows: (1) Preparation of functionalized graphene@basalt fiber particles ① Using chemical grafting method to in-situ modify the graphene surface with silane coupling agent and sulfur to obtain a bifunctional modified graphene dispersion; ② Add basalt fiber particles treated with different impregnants into the bifunctional modified graphene dispersion, the mass ratio of basalt fiber particles to graphene (solid state) is 20:1-50:1, adjust the pH to 10-12, stir at room temperature for 1-3 hours, and then filter and remove the residue after sand grinding to obtain a mixed solution of functionalized graphene@basalt fiber particles; (2) Preparation of graphene@basalt fiber / rubber composites ① Using the mixed solution of functionalized graphene@basalt fiber particles obtained in step (1) as a dispersion, adding a certain amount of natural latex; wherein the mass ratio of graphene@basalt fiber particles (solid mass) to natural latex is 1:2-1:5, mechanically stirring at room temperature for 1-3 hours to obtain a stable graphene@basalt fiber / natural latex suspension, flocculating with calcium chloride solution, repeatedly washing until neutral, and drying to prepare graphene@basalt fiber / natural rubber masterbatch; ② Taking natural rubber as the matrix material, the graphene@basalt fiber / natural rubber masterbatch with different contents is added to control the graphene@basalt fiber composite particles to be a variable of 10 to 40phr; wherein, the compounding agent is 3-5 parts of zinc oxide, 1-2 parts of stearic acid, 0.5-1 parts of accelerator D, 0.5-1 parts of accelerator DM, and 1.5-3 parts of sulfur; the graphene@basalt fiber / natural rubber mixture is prepared by a melt method, the vulcanization conditions are 145°C, 10MPa, and the time is the positive vulcanization time T90, and the graphene@basalt fiber / natural rubber composite material is prepared.
2. The preparation method according to claim 1, characterized in that: The specific operation of step (1) is as follows: S1 ultrasonically disperses the aqueous dispersions of graphene with different oxygen contents at room temperature to obtain graphene dispersions; S2: adding a certain amount of silane coupling agent to the graphene dispersion, stirring and reacting for 1-3 hours at a certain temperature to obtain a silane coupling agent-modified graphene dispersion; S3: adding a certain amount of Na2S2O3 aqueous solution to the silane coupling agent modified graphene dispersion of step S2, stirring and mixing for 1 hour; S4: adding a certain amount of hydrochloric acid to the mixed solution, and continuing to stir at room temperature for 2 hours after the addition is completed, so as to form bifunctional modified graphene double-modified with silane coupling agent and sulfur particles.
3. The preparation method according to claim 2, characterized in that: Step S1: The oxygen content in the aqueous dispersion of graphene with different oxygen contents is 10%-25%; the concentration of the aqueous dispersion of graphene with different oxygen contents is 2mg / mL-6mg / mL.
4. The preparation method according to claim 2, characterized in that: In step S2, the amount of silane coupling agent used is 2%-6% of the mass of graphene; the stirring reaction temperature is 60-90°C.
5. The preparation method according to claim 2, characterized in that: In step S3, the concentration of the Na2S2O3 aqueous solution is 0.4-0.8 mmol / mL, and the amount of Na2S2O3 used is 2%-6% of the mass of graphene; in step S4, the molar ratio of hydrochloric acid to Na2S2O3 is 1:
4.
6. The preparation method according to claim 1, characterized in that: In step (2), the natural rubber in ② is replaced by mixed rubber, and the weight proportion of the mixed rubber is: 20-50 parts of natural rubber, 20-50 parts of butadiene rubber, and 20-50 parts of styrene-butadiene rubber.
7. The preparation method according to claim 1, characterized in that: The basalt fiber particles treated with different impregnants in step (2) are basalt fiber particles for asphalt, basalt fiber particles for cement, basalt fiber particles with roving for profiles, or basalt fiber particles with roving for textiles.
8. A laminated conveyor belt, characterized in that: The method is prepared by any one of claims 1 to 7.
9. The laminated conveyor belt according to claim 8, characterized in that: The preparation operation is as follows: The conveyor belt is made of basalt fiber cloth treated with rubber as the core skeleton material, and graphene@basalt fiber / rubber composite material as the core rubber and cover rubber.
10. The laminated conveyor belt according to claim 9, characterized in that: The specific preparation operation is as follows: graphene @ basalt fiber / rubber composite material is used as the core rubber and cover rubber of the laminated conveyor belt, basalt fiber cloth is used as the core skeleton material of the laminated conveyor belt, and the multi-layer sandwich laminated rubber conveyor belt structure is arranged on the calender, and the basalt fiber cloth is 1, 3, 5 odd layers; the vulcanization conditions are 135 ~ 150 ℃, the vulcanization pressure is 1 ~ 3MPa, and the vulcanization time is 30 ~ 60 minutes.
Citation Information
Cited By
Pressure-resistant and fracture-resistant high-strength gypsum batten
CN120425856A
High-strength gypsum lath with pressure and bending resistance
CN120425856B